Indeks massa tubuh, asupan vitamin D, dan serum 25-hydroxyvitamin D pada pasien kanker payudara - Amilia Yuni Damayanti; Dono Indarto; Brian Wasita; Tonang Dwi Ardyanto (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2017)
Background: Breast cancer is the most common malignancy in women in the world. Vitamin D helps control the majority of gene expression in female reproductive tissues. Body mass index (BMI) influences the bioavailability of vitamin D. Diet is one of the main sources of vitamin D and it is directly converted into 25-hydroxyvitamin D [25 (OH) D] in the liver.Objective: This study aimed to analyze the relationship between BMI and vitamin D intake and 25 (OH)D serum in patients with breast cancer.Method: Analytic observational with cross sectional design was used in this study. A total of 37 breast cancer patient visited Dr. Moewardi Hospital in Surakarta was selected as research subjects using a purposive sampling technique. BMI data was obtained by measuring body weight and height. Vitamin D intake was determined using 1 x 24-hour food recall and semi-quantitative food frequency questionnaire. While, 25(OH)D serum was measured using enzyme-linked immunoabsorbent assay. Data analysis used Spearman correlation test.Results: The averages of BMI, vitamin D intake and 25(OH)D serum of breast cancer patients were 21.96±3.63 kg/m², 3.50±3.30 µg/day and 16.01±14.67 ng/mL respectively. Most breast cancer patients had less vitamin D intake and 25(OH)D serum deficiency. There was a weak relationship between BMI (r=0.188, p=0.266) and vitamin D (r=0.113, p=0.507) and 25 (OH)D serum in breast cancer patients.Conclusion: There were no significant correlations between BMI and vitamin D intake with 25(OH)D serum in breast cancer patients. Further study is required on the effect of chemotherapy regimens on vitamin D metabolism.